2015
DOI: 10.4314/bajopas.v8i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Hepatitis B co-infection in patients with febrile illnesses attending general outpatient unit of the Murtala Muhammed Specialist Hospital, Kano, Northwest Nigeria

Abstract: Malaria and Hepatitis B Virus (HBV) infections are co-endemic throughout much of the tropical and sub-Saharan Africa and both present major threat to public health. A study on the prevalence of HBV and Malaria co-infection was carried out on 200 patients presenting with fever at the General Outpatient Department (GOPD) of the Murtala Muhammed Specialist Hospital (MMSH), Kano using Gold Standard microscopy and rapid diagnostic test (RDT). The effect of mono and co-infection on hematological parameters was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
13
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 18 publications
11
13
3
Order By: Relevance
“…The study also showed that the highest rate of malaria infection was observed in subjects in the 21 -30 year age range (55.66%). This agrees with the finding of some earlier work (7,14,17) who reported a higher malaria prevalence among the same age group and contrary to reports (13,18) where age group 1 -10 years had the highest malaria infection rate. We had a larger population of people within this age group who took part in the study; in addition, it's been observed by WHO findings that young people living in malaria endemic zones are more vulnerable and prone to infection with malaria than the elder ones (21).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The study also showed that the highest rate of malaria infection was observed in subjects in the 21 -30 year age range (55.66%). This agrees with the finding of some earlier work (7,14,17) who reported a higher malaria prevalence among the same age group and contrary to reports (13,18) where age group 1 -10 years had the highest malaria infection rate. We had a larger population of people within this age group who took part in the study; in addition, it's been observed by WHO findings that young people living in malaria endemic zones are more vulnerable and prone to infection with malaria than the elder ones (21).…”
Section: Discussionsupporting
confidence: 92%
“…The study also documented a prevalence rate of 6.0% for HBsAg, which is contrary to 19.0% reported from Ilorin (8), but is consistent with a 6.5% and 5.1% prevalence rate reported from the North and South, respectively (7,16). The finding here is in line with the assertion that HBV infection is on the alarming increase (23) with the prevalence ranging from 3.9% to 50.7%.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations